Effect of polyethylene-grafted maleic anhydride (PE-g-MAH) on properties of low density polyethylene/eggshell powder (LDPE/ESP) composites - Supri, Abd Ghani; Ismail, H.; Shuhadah, S. (Taylor & Francis Group, LLC., 2010)
Link to publisher's homepage at http://www.informaworld.com/